The Direction of Papua Development: Is A New Autonomous Region the Answer? - Fadhli Zul Fauzi; David Erwin Mayor; Gasper Liauw (Policy & Governance Review, 2023)
This study aims to show what kind of problems and challenges occur in the middle of Papua Province development, as well as the extent of complexity of these development problems and the challenges of the New Autonomous Region to answer it. We use the systematic literature review method by showing a collection of literature from the Scopus database that discusses the development of Papua and analyzing the literature collection into several clusters. Bibliometric analysis is used to generate statistical models that show the relationship between each study. 151 literature sources were used in this study and produced three clusters namely development process, environment, and communication. From these aspects, several development efforts have been carried out by the government such as collaboration with the private sector, community capacity building through local value development, and the involvement of indigenous peoples. Moreover, there are several things that need to be considered such as land acquisition issues, the difficulty of access, planning and control functions, political intervention and interests, along with the communication system that has not been integrated. The New Autonomous Region can have a narrow span of control so it will optimize supervision and monitoring functions, but there are several things that need to be considered when implementing it such as planning, existing human resources capacity, and financial aspects. There are some limitations in this paper, where we cannot reach some highland areas to directly observe the challenges that occur there. Future research can develop discussions about Papua development through direct observations in those areas.